Optimal Hybrid Renewable Energy Integration for Reliable and Cost Efficient of Isolated System - Ardhyantoro, Novan Iman; Husnayain, Faiz (Faculty of Engineering, Universitas Tanjungpura, 2025)
Nusmapi Island is one of Indonesia's isolated islands that rely on Diesel Power Plant (PLTD) with a capacity of 20 kW to meet the electricity needs of its 50 customers. However, this PLTD only operates 12 hours a day due to high operational costs, reaching IDR 215,240,980/year with fuel consumption of 20,889 liters of diesel, equivalent to 17.56 tons with a COE of IDR 7,132/kWh in 2023. The reliance on diesel generators exacerbates ecological harm by releasing COâ‚‚ emissions